2010
DOI: 10.1007/s10554-010-9665-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional strain analysis of the global and regional myocardial function for the differentiation of pathologic and physiologic left ventricular hypertrophy: a study in athletes and in patients with hypertrophic cardiomyopathy

Abstract: Two-dimensional strain (2DS) is a novel method to measure strain from standard two-dimensional echocardiographic images by speckle tracking, which is less angle dependent and more reproducible than conventional Doppler-derived strain. The objective of our study was to characterize global and regional function abnormalities using 2DS and strain rate analysis in patients (pts) with pathological left ventricular hypertrophy (LVH) caused by non-obstructive hypertrophic cardiomyopathy (HCM), in top level athletes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 30 publications
5
61
1
1
Order By: Relevance
“…[7][8][9][10] Most notably, GLS and derived strain rate parameters can be measured, which have been shown to provide additional and valuable information beyond EF in different clinical scenarios, such as in subjects with coronary artery disease, heart failure, and cardiomyopathies. 9,10,21,22 Specifically, Di Salvo et al 23 showed that in hypertrophic cardiomyopathy, reduction in regional myocardial strain in more than three segments might identify patients at risk for ventricular arrhythmias; additionally, and of relevance to our purpose, Butz et al 11 recently showed that GLS can distinguish the physiologic hypertrophy of athlete's heart from hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[7][8][9][10] Most notably, GLS and derived strain rate parameters can be measured, which have been shown to provide additional and valuable information beyond EF in different clinical scenarios, such as in subjects with coronary artery disease, heart failure, and cardiomyopathies. 9,10,21,22 Specifically, Di Salvo et al 23 showed that in hypertrophic cardiomyopathy, reduction in regional myocardial strain in more than three segments might identify patients at risk for ventricular arrhythmias; additionally, and of relevance to our purpose, Butz et al 11 recently showed that GLS can distinguish the physiologic hypertrophy of athlete's heart from hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 95%
“…[7][8][9][10] Specifically, strain analysis may identify subclinical myocardial impairment (such as in incipient heart failure, ischemic heart disease, and valvular heart disease) and may be helpful in the clinical scenario of distinguishing physiologic from pathologic LV hypertrophy. [8][9][10][11][12][13] The aims of the present study were therefore to define the characteristics of LV myocardial mechanics as assessed by 2D STE in trained athletes and to derive reference values that may be implemented in the clinical assessment of ''athlete's heart. ''…”
mentioning
confidence: 99%
“…In experimental models and animal studies this new method has been validated against sonomicrometry and tagged MRI [7,8]. There is also some experience with STE in healthy humans and in various structural heart diseases such as hypertrophic cardiomyopathy (HCM), myocardial infarction, atrial septal defects (ASD), or LV dysfunction with conduction disorders in the context of cardiac resynchronization therapy (CRT) [4,[9][10][11][12][13][14][15][16]. However, all these reports were only based on small numbers of healthy probands or controls, had incomplete coverage of the LV, and/or focussed on specific cardiac problems.…”
Section: Introductionmentioning
confidence: 99%
“…In the future, a new technique that may help to differentiate physiological from pathological hypertrophy is the use of ultrasound speckle tracking; this calculates the global longitudinal strain in the ventricular muscle (Butz et al 2011). Differentiation of transient from long-term pathologies may also emerge from ultrasound and magnetic resonance imaging of right ventricular and atrial dimensions before and after endurance competition (Neilan et al 2006).…”
Section: Echocardiographymentioning
confidence: 99%